Surgical management of benign tumors of the parotid gland: the advantages of extracapsular dissection compared to traditional surgical techniques - Antonio Zanghì; Andrea Cavallaro; Martine Marchi; Marcello Marchi; Luigi La Via; Luigi La Via; Filippo Sanfilippo; Filippo Sanfilippo; Alessandro Cappellani; Simone Di Majo (Frontiers in Surgery)
IntroductionSalivary gland tumors represent only 3%–6% of all head and neck neoplasms, and approximately 70% of these tumors are located in the parotid gland. Most of these tumors are found in the more abundant superficial portion of the parotid gland, lateral to the facial nerve (FN). For many years, the location of the facial nerve between the superficial and deep segments of the parotid gland hindered adequate tumor extirpation. Several surgical options are available for the treatment of benign tumors in the parotid gland, but there remains no universal agreement on what the optimal surgical treatment is. In the early twentieth century, tumor enucleation was the standard treatment for parotid tumors to preserve the facial nerve, but high recurrence rates were the main downside of this procedure. To improve the outcome, superficial parotidectomy (SP) was implemented, which involves excision of the entire lateral segment of the parotid gland, superficial to the facial nerve. However, this surgical procedure may lead to severe postoperative complications, including facial nerve paralysis, in a significant number of patients. In recent years, more gland-preserving techniques were developed to reduce complication rates and improve the safety of procedures and patients' satisfaction, without increasing the risk of recurrence.Materials and methodThis study compares our surgical experience with extracapsular dissection gland-sparing surgery (ECD) to traditional superficial parotidectomy in 56 patients who underwent surgery performed by the same surgical team.ResultsThe superiority of ECD procedures compared to SP procedures was shown as far as total complication rates are concerned. In this case, Fisher's exact test statistic value was 0.0043 (significant at P < 0.05).ConclusionECD should be applied in properly selected cases and further prospective studies are needed to clarify the optimal indications.